Peritumoral EpCAM Is an Independent Prognostic Marker after Curative Resection of HBV-Related Hepatocellular Carcinoma. (10th May 2017) - Dai, Xiao-Meng; Huang, Tao; Yang, Sheng-Li; Zheng, Xiu-Mei; Chen, George G.; Zhang, Tao
Abstract : Accumulating evidence suggests that the tumor microenvironment has a profound influence on tumor initiation and progression, opening a new avenue for studying tumor biology. Nonetheless, the prognostic values of the peritumoral expression of EpCAM and CD13 remain to be elucidated in hepatocellular carcinoma (HCC) patients. In this study, the expression of EpCAM and CD13 was assessed by immunohistochemistry in peritumoral liver hepatocytes from 106 hepatitis B virus- (HBV-) related HCC patients who had undergone curative hepatectomy. The peritumoral EpCAM-positive group had a significantly worse overall survival (OS) (p = 0.003 ) and recurrence-free survival (RFS) (p = 0.022 ) compared to the negative group. Peritumoral CD13-positive patients were also associated with poor OS (p = 0.038 ), while not significantly associated with RFS. The adjusted multivariate COX proportional hazard regression analysis suggested that only the positive expression of peritumoral EpCAM precisely predicted poor OS. Being peritumoral EpCAM positive was also significantly associated with a larger tumor size, liver cirrhosis, and more frequent vascular invasion; however, no statistically significant association was observed between CD13 and any clinicopathological features. Taken together, peritumoral EpCAM and CD13 expression was associated with a poor prognosis, but EpCAM may be a better prognostic marker than CD13 in HBV-related HCC patients. In the future, peritumoral EpCAM could be a good target for adjuvant therapy after curative hepatectomy.